Female medical students' awareness, attitudes, and knowledge about early detection of breast cancer in Syrian Private University, Syria. Issue 4 (April 2020) - Omar, Abdullah; Bakr, Aliaa; Ibrahim, Nazir
Abstract: Introduction: Breast cancer is the most frequent cancer among women, impacting 2.1 million women each year, and also causes the greatest number of cancer-related deaths among women. The study aims to determine the community awareness levels in our country and extrapolate knowledge and awareness about the methods of early detection. Methods: It was performed as cross-sectional study in Syrian Private University in Damascus, Syria from January to March 2019. The population included female students of all years in medical faculties: medicine, pharmacy and dentistry collages. Data collection have been done by breast cancer awareness measure (BCAM) questionnaire. Results: The total participants were 407 divided into three faculties. The average knowledge rate was (57.5%). (70 %) of participants were not familiar with mammography. It is a good result that (86.7 %) acquainted about self-examination and (94.8%) believe that it is very important. But it is obvious that the practical side is poor, there were (32.7%) of students who apply BSE. Conclusion: This study showed a lack of awareness among medical students. Perhaps the most important reason is the lack of awareness programs that must include all strata of society, especially students of medical colleges and doctors for their important role in spreading awareness to avoid this danger that surrounds our ladies. Abstract : Health sciences; Public health; Women's health; Oncology; Clinical research; Medical students; Breast cancer; Acknowledge; Awareness; Syria.